Cystobacter fuscus HM-E: a novel biocontrol agent against cotton Verticillium wilt - Jian Han; Jian Han; Jian Han; Meili Shi; Meili Shi; Meili Shi; Xinyu Dou; Xinyu Dou; Xinyu Dou; Wen Pan; Wen Pan; Wen Pan; et al. (Frontiers in Microbiology)
Verticillium wilt of cotton, caused by Verticillium dahliae, is one of the most devastating soilborne fungal diseases in cotton production, urgently demanding the development of effective control measures. Myxobacteria, a group of higher prokaryotes exhibiting multicellular social behaviors, possess predatory activity against plant pathogenic fungi and bacteria, giving them unique potential for application in plant disease biocontrol. In this study, based on a previously myxobacterial strain collection, a myxobacterial strain, HM-E, exhibiting broad-spectrum antifungal activity was screened. Through morphological observation, physiological and biochemical characterization, and multi-locus sequence analysis, this strain was identified as Cystobacter fuscus HM-E. C. fuscus HM-E not only significantly lysed V. dahliae hyphae but also inhibited its spore germination. Both its cell-free fermentation filtrate and volatile metabolites exhibited certain antifungal activity. Greenhouse pot assays showed that the fermentation broth of C. fuscus HM-E had a control efficacy of only 23.01% against cotton Verticillium wilt, whereas the solid agent formulated with white star flower chafer (Protaetia brevitarsis) frass achieved a significantly higher control efficacy of 70.90%, and the myxobacterial solid agent also significantly promoted cotton seedling growth. Furthermore, the crude extracts concentrated using macroporous resin and acid precipitation showed no antifungal activity against V. dahliae, whereas the crude protein obtained by ammonium sulfate precipitation disrupted not only the cell wall and cell membrane of V. dahliae hyphae, induced intracellular reactive oxygen species (ROS) burst but also lysed spores and inhibited spore germ tube elongation. Enzyme substrate profile assays indicated that several peptidases, lipases, and glycoside hydrolases secreted by C. fuscus HM-E might play important roles in its antifungal process and are potential biocontrol factors. This study suggests C. fuscus HM-E, as a novel biocontrol agent, has great potential for application in the combating of cotton Verticillium wilt.